Impact of Insertion Technique and Iliac Artery Anatomy on Fenestrated Endovascular Aneurysm Repair. (December 2019) - Crawford, Sean A.; Doyle, Matthew G.; Amon, Cristina H.; Forbes, Thomas L.
Purpose: To develop a mechanically realistic aortoiliac model to evaluate anatomic variables associated with stent-graft rotation and to assess common deployment techniques that may contribute to rotation.Materials and Methods: Idealized aortoiliac geometries were constructed either through direct 3-dimensional (3D) printing (rigid) or through casting with polyvinyl alcohol using 3D-printed molds (flexible). Flexible model bending rigidity was controlled by altering wall thickness. Three flexible patient-specific models were also created based on the preoperative computed tomography angiograms. Zenith infrarenal and fenestrated devices were used in this study. The models were pressurized to 100 mm Hg with normal saline. Deployments were performed under fluoroscopy at 37°C. Rotation was calculated by tracking the change in position of gold markers affixed to the devices.Results: In the rigid idealized models, stent-graft rotation increased with increasing torsion; torsion levels of 1.6, 2.6, and 3.6 mm −1 had mean rotations of 5.2°±0.03°, 11.2°±4.8°, and 27.6°±13.0°, respectively (p<0.001). In the flexible models, the highest rotation (58°±3.0°) was observed in models with high torsion and high rigidity (7.5 mm −1 net torsion and 254 N·m 2 flexural rigidity). No rotation was observed in the absence of torsion. Applying torque to the device during insertion significantly increased stent-graft rotation by an average of 28° across all levels of torsion (p<0.01). Multiple device insertions prior to deployment did not change the observed device rotation. The patient-specific models accurately predicted the degree of rotation seen intraoperatively to within 5°.Conclusion: Insertion technique plays an important role in the degree of stent-graft rotation during deployment. Our model suggests that in vivo correction of device orientation can increase the observed rotation and supports the concept of fully removing the device, adjusting the orientation, and subsequently reinserting. Additionally, increasing iliac artery torsion in the presence of increased vessel rigidity results in stent-graft rotation.